Monothermal Caloric Screening Test Accuracy: A Systematic Review. (1st March 2016) - Adams, Meredith E.; Telian, Steven A.; Kane, Robert L.; Butler, Mary
Abstract : Objective: To minimize discomfort, time, and costs, vestibular laboratories may perform monothermal caloric irrigations and discontinue testing if responses are symmetric. This systematic review aimed to determine the diagnostic accuracy of the monothermal caloric screening test (MCST) for unilateral vestibular dysfunction compared with bithermal caloric testing (BCT). Data Sources: Ovid‐MEDLINE, EMBASE, Scopus, Cochrane CENTRAL, and manual bibliographic searches. Review Methods: Inclusion criteria specified concurrent MCST and BCT performance and reporting of test measures (monothermal caloric asymmetry, unilateral weakness). The primary outcomes were between‐measure correlation, sensitivity, and specificity. Meta‐analysis was performed with hierarchical bivariate and univariate random‐effects models. Heterogeneity was assessed with the I 2 statistic. Results: Fifteen studies (n = 5572 participants) met inclusion criteria. Thresholds varied between studies. Asymmetries calculated by MCST and BCT were strongly correlated, but a subgroup analysis showed no correlation for those with mild unilateral weakness. The sensitivity and specificity of the MCST ranged from 0.54 to 1.00 and 0.25 to 0.96, respectively. Predictably, higher sensitivity resulted from lower cutoff points for the MCST, higher thresholds for the BCT, and additional test positivity criteria. Warm irrigations yielded higher sensitivity than cool. Studies excluding participants with severe unilateral weakness yielded lower sensitivity estimates. After pooling by threshold, temperature, and risk of bias, most performance estimates remained substantially heterogeneous ( I 2 > 60%). Conclusion: Accuracy of the MCST is lacking precisely where it is needed most—at the border of normal and abnormal vestibular function. To guide clinical practice, research should include analysis of subgroups with varying levels of function and employ standardized testing parameters.